Dicroidium (foliage) and affiliated wood Part 3 of a reassessment of Gondwana Triassic plant genera and a reclassification of some previously attributed. Issue 1 (2nd January 2020) - Anderson, Heidi M.; Barbacka, Maria; Bamford, Marion K.; Holmes, W. B. Keith; Anderson, John M.
Abstract : Anderson, H.M., Barbacka, M., Bamford, M.K., Holmes, W.B.K. & Anderson, J.M., 10 July 2019. Dicroidium (foliage) and affiliated wood; Part 3 of a reassessment of Gondwana Triassic plant genera and a reclassification of some previously attributed. Alcheringa 44, 64–92. ISSN 0311-5518 Dicroidium belonging to Umkomasiaceae (Corystospermaceae) in the polyphyletic pteridosperms (seed-ferns) is reassessed comprehensively worldwide and emended. All records are analysed and some attributed to the genus previously are reclassified. Dicroidium leaves are clearly affiliated with Umkomasia 'megasporophylls' and Pteruchus 'microsporophylls'. The attachments of Dicroidium leaves to stems and associated wood genera are reviewed. Dicroidium is shown to be restricted to the Triassic of Gondwana, where it is by far the most prominent and diverse genus with 23 accepted species. It is well represented in collections from South America, Antarctica, India, Australia, New Zealand and southern Africa from where the Molteno Formation is the most comprehensively sampled stratigraphic unit, yielding numerous species from 75 assemblages. The problems of defining the limits of Dicroidium and its species are addressed. The records of leaf fragments from the Indian Nidpur Flora, Early Triassic, are questionably referable to Dicroidium, whereas the multiple forking leaves from the Cisuralian of India await description as a new peltasperm genus. The forked leaves from the (?)Lopingian of Jordan, previously classified as Dicroidium, are reassessed and placed in the new genus Jordaniopteris. Heidi M. Anderson [hmsholmes@googlemail.com ], Evolutionary Studies Institute, University of the Witwatersrand, Johannesburg 20150, South Africa; Maria Barbacka [maria.barbacka@gmail.com ], W. Szafer Institute of Botany, Polish Academy of Sciences, Lubicz 46, Kraków 31-512, Poland, Botanical Department, Hungarian Natural History Museumartmem H-1431, Budapest, Pf. 137, Hungary; Marion K. Bamford [marion.bamford@wits.ac.za ], Evolutionary Studies Institute, University of the Witwatersrand, Johannesburg 20150, South Africa; W. B. Keith Holmes [wbkholmes@hotmail.com ], 46 Kurrajong Street, Dorrigo, NSW 2453, Australia, University of New England, Armidale, NSW 2351, Australia; John M. Anderson [jmanderson.gondwana@googlemail.com ], Evolutionary Studies Institute, University of the Witwatersrand, Johannesburg 20150, South Africa.